Marker Haplotype Construction for the Hybrid Necrosis Gene Ne2 and Its Distribution in Old and New Wheat Varieties - Volker Mohler; Adalbert Bund; Lorenz Hartl; Theresa Albrecht (Crops)
Hybrid necrosis in wheat is caused by an interaction between two genes, Ne1 and Ne2, that triggers the gradual death of plant tissue. This trait affects wheat breeding as the gene Ne2 is the same as the gene Lr13 for leaf rust resistance. We have built a three-marker haplotype that consists of single nucleotide polymorphism (SNP) marker information already available on genotyping arrays for the determination of the presence and absence of Ne2. In this work, test crosses of eight bread wheat varieties with known and unknown Ne1 carriers showed that six of them possessed Ne2. We analyzed a set of wheat varieties which had partial SNPs and phenotypic data, i.e., hybrid necrosis and leaf rust reactions, using Kompetitive Allele-Specific PCR (KASP) markers previously available for Ne2. The observed haplotypes of the SNP markers RAC875_c1226_652, Ra_c4397_542, and AX-110926324 perfectly matched the KASP marker variants for Ne2 and ne2. A prediction, based on these SNP haplotypes, of the distribution of Ne2 in wheat varieties, predominantly from Germany and released between 1900 and 2024, showed that breeding steadily increased the proportion of Ne2 in the German gene pool.